2005
DOI: 10.1021/jo051148+
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Electroreductive Cyclization and Electrohydrocyclization Using Catalytic Reduced Nickel(II) Salen

Abstract: [Chemical reaction: See text] We describe efforts to achieve the electroreductive cyclization (ERC) and the electrohydrocyclization (EHC) reactions using catalytic nickel(II) salen as a mediator. While nickel(II) salen proved effective, the analogous cobalt complex as well as nickel(II) cyclam were not. The transformations were achieved in yields ranging from 60 to 94% using either a mercury pool or an environmentally preferable reticulated vitreous carbon (RVC) cathode. These examples represent the first inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 39 publications
5
57
0
Order By: Relevance
“…This conclusion has been buttressed by the results of several low-temperature studies by means of EPR spectroscopy [5,55,81]. However, recent work [41,59] has provided compelling evidence that a ligand-based reduction, involving the imino (C@N) bonds of nickel salen, can occur to form the following species:…”
Section: Metal-centered Versus Ligand-centered One-electron Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion has been buttressed by the results of several low-temperature studies by means of EPR spectroscopy [5,55,81]. However, recent work [41,59] has provided compelling evidence that a ligand-based reduction, involving the imino (C@N) bonds of nickel salen, can occur to form the following species:…”
Section: Metal-centered Versus Ligand-centered One-electron Reductionmentioning
confidence: 99%
“…Additional papers have appeared from the laboratories of Helvenston and Castro [18], Fry and Fry [21], Esteves and co-workers [32], and Gennaro and Isse [34,36]. Recently, it has been shown that a reduced form of nickel(II) salen, with electron density on the imino bonds of the ligand, can promote the electroreductive cyclization of the methyl ester of (E)-8-oxo-oct-2-enoic acid [41].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of established mechanistic pathways [17][18][19][20]22 and our current findings, a possible mechanism for the nickel(I) salen-catalyzed reduction of the two aryl halides is proposed in Scheme 2. The electrogenerated metal-reduced nickel(I) (2) or the ligand-reduced radical鈭抋nion (3) can transfer one electron to the substrate, which undergoes reductive cleavage of the carbon鈭抌romine bond to form the corresponding radical and regenerates nickel(II) salen (1) (reaction 1).…”
Section: Comparison Of Cyclic Voltammograms For the Nickel(ii) Salen mentioning
confidence: 90%
“…Nevertheless, the former cathodic wave easily vanished while being detected without any further inert gas protection through bubbling N. This wave repeatedly appeared when detected under N 2 atmosphere. This phenomenon manifested that complex 1 was an oxidant-hypersensitive substance that easily reacts with oxidant components, such as O [27]. Furthermore, no cathodic waves (I red ) in complexes 2 and 3 were observed, except the reduction wave (II red ).…”
Section: Electrochemical Behaviormentioning
confidence: 98%